Structuring scientific works in the “Introduction, Methods, Results and Discussion” format – what a beginner ought to know - N. V. Avdeeva; G. A. Lobanova (Открытое образование (Москва), 2016)
Reference materials about the “Introduction, Methods, Results and Discussion”, which is a commonly used international format for scientific works, have become available for Russian authors nowadays, still lack of knowledge about the format would pop up here or there, especially when we speak about beginners. The faults which would appear regularly in work structuring prompted the present research, the aim of which is to compare the information about the IMRAD format with the specific difficulties beginning authors would often face when preparing their works for publication.The main materials to be studied were sources in Russian and in English published mostly in 2010s and devoted to the problems of structuring works according to the meant above format. Besides, the present research considered the results of plagiarism tests (such tests used to be carried out at the Russia State Library within the period of 2013 – 2015 with the help of software “Automated system of specialized processing of textual documents”). The main methods of our research would remain structural and comparative analysis of texts.As a result, our research revealed the fact of inconsistency of the available information on the IMRAD structure. It would often demand deep thinking and explanations. Different authors of reference editions would as a rule differ one from another in their interpretation of the degree of necessity of this or that composition element, of the amount of details in descriptions, etc. Moreover, the very structure of scientific work looks differently for different authors. More often the structure supposes the integrity of the contents and its form, still sometimes its description would be replaced by outer elements, such as, for example, language clichés. The analysis of the most common faults in text structuring points that authors do not often have a clear idea of how to understand the different demands which are so obscurely described.The research carried out leads to the conclusion that at present the available sources on preparation of publications could only help those beginners who are used to thinking profoundly and taking everything seriously, this including their own research activity.